If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4(-3x + 2) = 136 Reorder the terms: 6x + -4(2 + -3x) = 136 6x + (2 * -4 + -3x * -4) = 136 6x + (-8 + 12x) = 136 Reorder the terms: -8 + 6x + 12x = 136 Combine like terms: 6x + 12x = 18x -8 + 18x = 136 Solving -8 + 18x = 136 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 18x = 136 + 8 Combine like terms: -8 + 8 = 0 0 + 18x = 136 + 8 18x = 136 + 8 Combine like terms: 136 + 8 = 144 18x = 144 Divide each side by '18'. x = 8 Simplifying x = 8
| 8+5w=-17 | | X^5-6=0 | | 1.33x+0.5x+0.16x=2 | | -17+3n=7n-14 | | x+3=-30+6 | | -94=-6(b+4)-4b | | 12x-4=-68 | | 2(x-6)=x+14 | | 11x-88-11=27x-275 | | 10=12x-11x-17 | | -1(f+20)=7 | | 75=3(-12x-3) | | -2(1+7x)+5(x-5)=10x-10-2x | | -7x=-34 | | 2x^3y-10x^2y-6xy= | | 2x+x-9=-45 | | 5u^2-240=0 | | -8x-29+10x=9 | | f(x)=4e^3x+2 | | 2sinx-6=0 | | -28+2n=4(6n-7) | | 5h^2+400=0 | | 6y=7+5y | | X^2-8*x+7=0 | | 3x-5x=23-15 | | 13-4x-7x=18x+14 | | m^6=16m^4 | | 3(x-4)2=3(x-1)-7 | | 32x+5=3x-3 | | 7-3x=2x+27 | | pH=-log[5.7*10(-4)] | | 11x-85+x=167 |